The relationships between self-esteem, parental behavior with economic hardship among single mothers in Kota Kinabalu, Sabah - Joki Perdani Sawai; Kwan, Sharon Sam Mee; Zall Kepli MD Rejab; Balan Rathakrishnan (Universiti Malaysia Sabah, 2010)
this quantitative research attempts to examine the relationships between economic hardship, self-esteem, and parental behavior among single mothers. Specifically, the objectives of this research are to: 1) measure the relationship between economic hardship and self-esteem; 2) measure the relationship between economic hardship and parental behavior; 3) measure the economic hardship, self-esteem and parental behavior, based on demographic variables which are age and level of income. The instrument consisted of three parts: Economic Strain Questionnaire (ESQ) was used to measure the economic hardship; Self-Esteem Inventories (SEI)to measure the self-esteem; and Parent's Report Scale (PRS) to measure parental behavior. The validity and reliability of the entire three instruments have been measured. The data of this research was analyzed using descriptive and inferential statistics the Statistical Packages for the Social Sciences (SPSS). The study showed that there was an insignificant negative relationship between economic hardship and self-esteem; there was a significant positive relationship between economic hardships with self-esteem and parental behavior. The study also indicated that there were insignificant differences economic hardship, self-esteem, and parental behavior based on age and level of income among these single mothers. Results are discussed and implications for future research directions also explored.